Siyasah Dusturiyyah Scrutiny of Village Financial Digitization per Permendagri No. 20/2018 Article 2(1): Empirical Insights from Darmaraja Village, Ciamis - Anggini Agestia Ibrahim; Beni Ahmad Saebani; Bobang Noorisnan Pelita (Jurnal Iman dan Spiritualitas, 2026)
This research is motivated by the phenomenon of the implementation of digital village financial management which has various implications for transparency, accountability, and village financial governance. In the perspective of Siyasah Dusturiyah, digital village financial management must be carried out with the mandate and efforts of Hifzh Al-Mal (protection of state assets) which must be accounted for. The purpose of this research is to describe the implementation of digital village financial management in Darmaraja Village and assess its effectiveness based on Article 2 Paragraph (1) of the Regulation of the Minister of Home Affairs Number 20 of 2018 and analyze its compliance with the principles of Siyasah Dusturiyah. This research uses an empirical juridical method through field observation. Data were obtained through literature reviews, documentation, and interviews with village officials, BPDs, community leaders, the DPMD of West Java Province, and the Regional Government Bureau of the Secretariat of West Java Province. The results of the study indicate that the implementation of Darmaraja village financial management has succeeded in creating an administrative discipline system for village officials. However, from the community perspective, low digital literacy is still an obstacle, so billboards are a viable solution to bridge the information gap. From the perspective of Siyasah Dusturiyah, this shows that successful digital village financial management must be accompanied by a change in work culture that prioritizes community welfare, ensuring that Hifzh Al-Mal efforts are realized not only administratively but also tangibly through inclusive transparency.